2017
DOI: 10.1097/ccm.0000000000002020
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Up-regulation in Human Amniotic Fluid Stem Cell Enhances Nephroprotection After Ischemia-Reperfusion Injury in the Rat

Abstract: Up-regulation of vascular endothelial growth factor enhances the therapeutic effect of human amniotic fluid stem cells in rats with renal ischemia-reperfusion injury, mainly by mitogenic, angiogenic, and anti-inflammatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…S7) than other factors. Interestingly, studies have shown that individual administration of follistatin , HGF , or VEGF is effective in accelerating tubular regeneration in animals with renal I/R. Follistatin treatment, through blocking activins or transforming growth factor‐beta superfamily members, reduced renal injury by I/R .…”
Section: Discussionmentioning
confidence: 99%
“…S7) than other factors. Interestingly, studies have shown that individual administration of follistatin , HGF , or VEGF is effective in accelerating tubular regeneration in animals with renal I/R. Follistatin treatment, through blocking activins or transforming growth factor‐beta superfamily members, reduced renal injury by I/R .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studying the pharmacokinetics of the distributed nanoparticles is important as well, but this will depend strongly on the exact characteristics of the given nanoparticle. For example, viral vectors on average can enter a target cell in a short time frame (minutes–hours), whereas for other nanoparticles such as stem cells it will be important that they can reside at the desired lung region for a longer time period (hours, days) . A next step towards the development of a preclinical animal model that allows long‐term evaluation of the administered nanoparticle will require the development of an optimal surgical procedure that allows survival of the operated sow and piglets.…”
Section: Discussionmentioning
confidence: 99%
“…We consider hAF-SC a good candidate for autologous perinatal therapy as amniotic fluid is accessible via amniocentesis or even at the time of birth. Expansion and cryopreservation of hAF-SC are easily performed [12], and the cells are permissive to genetic manipulation if necessary [10]. These cells have already been extensively studied in regenerative medicine applications.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 h, the survivors were randomized to 5 groups: normoxia (21% O 2 ; N), hyperoxia (95% O 2 ; H), hyperoxia + fibroblasts (HhFB), hyperoxia + hAF-SC (HhAF), or hyperoxia + hAF-SC-VEGF (HhAF-VEGF). Cells were administered intraperitoneally in a single dose on postnatal day (PN) 0 using 5 × 10 5 cells per pup dissolved in PBS to a total volume of 50 μL [10]. Sufficient pups were included to obtain at least 7 surviving pups on PN7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation